Hubungan Antara Dukungan Sosial Dengan Kebermaknaan Hidup Pada Guru SLB - Triyono, Agus (2016)
Abstraction. Great sacrifice a SLBteacher, that sincere devotion given to students and the profession most precisely give special value and thus deserves to be the goal of his life. The purpose of life that gives meaning to the person called byterms of life meaningfulness of meaningful. One of the factors which effect on the meaningfulness of life namely social support. The aim of this research is to know the relationship between social support with the meaningfulness of life, so the authors propose the hypothesis "there is a relationship between social support with the meaningfulness of life." The study was conducted by researchers at four SLB in the subdistrict of karanganyar, i.e. SDLB N of Karanganyar, SLB B YPALB of karanganyar, SLB C YPALB of Karanganyar and SLB of BinaKaryaInsaniof Karanganyar. Sampling technique was purposive non random sampling, that is subject that made the research samplesis basedof particular characteristic. Measuring instrument that used to reveal the research variables there are 2 kinds of measuring instrument, namely: (1) social support scale, and (2) the scale of the lifemeaningfulness. Data analysis in this study uses the product moment correlation. Based on the analysis results, then obtained the very significant correlation between the life meaningfulness withsocial support, which (r) amount of 0.296 with p = 0.001 where p < 0.01, this means there is a very significant positive relationship between social support with the life meaningfulness of teachers. This means that higher the level of social support, then the higher level of life meaningfulness of SLB teacher and vice versa, the lower levels of social support then also lower level the life meaningfulness of SLBteacher.The empirical mean of social support variables amount of 90.91 with hypotheticmean amount of 85.So the empirical mean>hypotheticmean which means in generallythe social supportare classified as medium. Furthermore the empirical mean of the variable life meaningfulness of the teacher namely amount of 67.8 with hypotheticmean amount of 65. So the empirical mean>hypothetic mean which means in generallythe subject posses the life meaningfulness of that also is medium. This research can be concluded that there is a very significant positive relationship between social support with the lifemeaningfulness. The role of the social support toward the life meaningfulness (SE) amount of 8.7%, sostill there is 91.3%another factor besides the social support that affect the meaningfulness of life. Key words: life meaningfulness, social support